The Effect of the Use of Augmented Reality (AR), Perceived Risk, and Trust on Online Shopping Behavior through Perceived Enjoyment on Local Cosmetic Products on Shopee - Mazaya Annida Jauza Safira; Ratna Listiana Dewanti (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study aimed to analyze the influence of the use of augmented reality, perceived risk, and trust through perceived enjoyment on online shopping behavior on local cosmetics on Shopee. The sampling in this research was purposive sampling of 157 respondents. The research employs quantitative data, with primary data collected through an online questionnaire that was tested for validity and reliability. The analysis tool used in this study had Structural Modelling-Partial Least Square (PLS-SEM). Hypothesis testing was conducted though path analysis. The R-square value for the Perceived Enjoyment variable obtained an R-square value of 0.533 and a customized R-square value of 0.524. Meanwhile, the Online Shopping Behavior variable obtained an R-square value of 0.593 and a customized R-square value of 0.585. The p-value results showed <0.05 so that the data analysis showed that augmented reality had a positive and significant effect on online shopping behavior, perceived risk had a positive and significant effect on online shopping behavior, trust had a positive and significant effect on online shopping behavior, augmented reality had a positive and significant effect on perceived enjoyment, perceived risk had a positive and significant effect on perceived enjoyment, trust had a positive and significant effect on Perceived enjoyment, perceived enjoyment had a positive and significant effect on online shopping behavior. Augmented reality had a positive and significant effect on online shopping behavior through perceived enjoyment, and perceived risk had a positive and significant effect on online shopping behavior through perceived enjoyment. The results of this research can be useful for online business people, especially local cosmetics, to be able to improve the customer shopping experience. Local e-commerce players need to integrate engaging AR technology, build trust with product guarantees and transparent reviews, and leverage risk perception as an element that adds excitement to the online shopping experience to drive consumer loyalty.